Elevated Steady State WBC and Platelet Counts Are Associated with Frequent Emergency Room Use in Adults with Sickle Cell Anemia. - Susanna A Curtis; Neeraja Danda; Zipora Etzion; Hillel W Cohen; Henny H Billett (PLoS ONE, 2015)
Sickle cell anemia has many sequelae that result in emergency department (ED) use, but a minority of patients with sickle cell disease are frequent utilizers and make up the majority of ED visits. If patients who are likely to be frequent ED can be identified in steady state, they can be treated with disease modifying agents in an attempt to reduce ED use frequency. We sought to identify steady state markers for frequent ED use.We identified all patients with SS/Sβ0 seen at our facilities in 2012. Health care utilization over the entire year was calculated and ED visit numbers categorized as either 0-1, 2-5, or 6 or more visits a year. Steady state and acutely active laboratory parameters were collected and analyzed using analysis of variance models and odds ratios.432 adult sickle cell patients were identified, ages 18-87, 54% female, and 38% had been prescribed hydroxyurea. Of the 432 patients,192 had 0-1 visits in the year, 144 had 2-5 visits in the year, and 96 had >6 visits for a total of 2259 visits. Those who had >6 visits accounted for 1750 (77%) of the total visits for the year. When steady state laboratory markers were examined, each additional 50x10(9)/L platelets was associated with 22% greater risk (p < .001); each 1x10(9)/L of WBC was associated with 11% greater risk (p = .003), and each 1g/dL Hb was associated with 23% lower risk (p = .007) of >6 ED visits/year. We did not observe a relationship between baseline HbF, LDH or reticulocyte count with >6 ED visits.Patients with elevated white blood cell counts, elevated platelet counts, and low hemoglobin levels exhibited higher risk for frequent ED utilization and could be candidates for early and aggressive therapy with disease modifying agents.